Miasta a efekt cieplarniany w świetle współczesnych ustaleń naukowych - Fortuniak, Krzysztof (Public participation in urban climate policy making: The example of Lodz, 2024)
Cities responsible for over 70% of global greenhouse gas (GHG) emissions are also areas with a high mitigation potential. The search for specific solutions enabling a significant reduction of GHG emissions in urban areas is therefore of key importance in the global pro-climate policy. One of the tools for this purpose may be discussions within the citizens’ assembly. The developed solutions, in order to be effective, must be consistent with the current state of knowledge. Therefore, the undertaken study provides basic information on the greenhouse effect and the role of individual greenhouse gases, methods for determining emissions from the city area and the characteristics of the urban climate. Particular attention was paid to the dangers resulting from the insufficiently thorough interpretation of the results obtained with the use of various GHG inventory methods. In terms of urban climate, the differences between the classic urban heat island regarding the air temperature in the city and the surface temperature obtained from satellite imagery were highlighted. The impact of the city on the precipitation and wind field was also characterized. Finally, urban strategies for mitigating climate change were discussed.